Wesley and the Wesleyans - Kent, John 1923- (Cambridge University Press, 2002)
Wesley and the Wesleyans challenges the cherished myth that at the moment when the Enlightenment and the Industrial Revolution were threatening the soul of eighteenth-century England, an evangelical revival - led by the Wesleys - saved it. It will interest anyone concerned with the history of Methodism and the Church of England, the Evangelical tradition, and eighteenth-century religious thought and experience. The book starts from the assumption that there was no large-scale religious revival during the eighteenth century. Instead, the role of what is called 'primary religion' - the normal human search for ways of drawing supernatural power into the private life of the individual - is analysed in terms of the emergence of the Wesleyan societies from the Church of England. The Wesleys' achievements are reassessed; there is fresh, unsentimental description of the role of women in the movement, and an unexpectedly sympathetic picture emerges of Hanoverian Anglicanism